O'Reilly Artificial Intelligence Conference 2019, London, United Kingdom. (O'Reilly Media, 2019)
"The Artificial Intelligence Conference London 2019 gathered some of the globe's top AI practitioners to speak about AI's most promising developments, emerging technologies, and profitable use cases. This video compilation provides you with the best that AI London 2019 had to offer. It includes thought provoking presentations from such AI luminaries as Ariadna Font Llitjós, the director of engineering at Twitter's Cortex Machine Learning Platform; Martin Goodson, the chief scientist at Evolution AI; Jeff Jonas, the founder and CEO of Senzing; Kim Hazelwood, the senior engineering manager who leads AI infrastructure research efforts at Facebook, and many more of AI's top data scientists, software engineers, and business strategists. AI is changing fast and it's transforming business even faster. To see where AI is going (and the entirely new business models and procedures it enables), get this compilation and you'll be ahead of the curve."--Resource description page.